Magnetic-Structural and Tectonic Framework in the Genesis Process and Evolution of Relief in the Central portion of the Araucárias Plateau - Lima, Jacson Gosman Gomes de; Pontelli, Marga Eliz; Santos-Matos, Andre; Guimarães, Suze Nei Pereira (Revista Brasileira de Geomorfologia, 2022)
Abstract: The structural and tectonic influence on the relief of a region can be studied based on subsurface magnetic structures, especially those correlated to the basement (deep structures) and shallow structures linked to geomorphological context, faults/fractures, and drainage network. Aiming to understand the structural and tectonic influence on the relief of the Araucárias Plateau, airborne magnetic geophysical data was processed using Oasis Montaj software (Geosoft TM, 2004) and used to generate magnetic anomaly maps. Interpretations of the vertical derivative applied to the anomalous magnetic field enabled the identification of 49 magnetic lineaments. The characteristics of these lineaments allowed to divide the study area into three distinct geotectonic compartments that are in agreement with the structural blocks of the Paraná basin. The results show that these magnetic lineaments mapped show directional agreement with shallow lineaments and, in many cases, constitute structures that extend from the basement to the surface. It was also possible to observe that the drainage network is adjusted to important mapped magnetic lineaments. This reinforces the importance of these structures in the genesis and evolution of the Araucárias Plateau. The analysis of magnetic lineaments, faults/fractures mapped, and geomorphological lineaments showed NW-SE orientations as the most important trend, suggesting that structures with this orientation exert the greatest influence on the relief in the study area.